Involvement of DNA Damage Response Pathways in Hepatocellular Carcinoma. (28th April 2014) - Yang, Sheau-Fang; Chang, Chien-Wei; Wei, Ren-Jie; Shiue, Yow-Ling; Wang, Shen-Nien; Yeh, Yao-Tsung
Abstract : Hepatocellular carcinoma (HCC) has been known as one of the most lethal human malignancies, due to the difficulty of early detection, chemoresistance, and radioresistance, and is characterized by active angiogenesis and metastasis, which account for rapid recurrence and poor survival. Its development has been closely associated with multiple risk factors, including hepatitis B and C virus infection, alcohol consumption, obesity, and diet contamination. Genetic alterations and genomic instability, probably resulted from unrepaired DNA lesions, are increasingly recognized as a common feature of human HCC. Dysregulation of DNA damage repair and signaling to cell cycle checkpoints, known as the DNA damage response (DDR), is associated with a predisposition to cancer and affects responses to DNA-damaging anticancer therapy. It has been demonstrated that various HCC-associated risk factors are able to promote DNA damages, formation of DNA adducts, and chromosomal aberrations. Hence, alterations in the DDR pathways may accumulate these lesions to trigger hepatocarcinogenesis and also to facilitate advanced HCC progression. This review collects some of the most known information about the link between HCC-associated risk factors and DDR pathways in HCC. Hopefully, the review will remind the researchers and clinicians of further characterizing and validating the roles of these DDR pathways in HCC.